Comprehensive Analysis of Factors Influencing Quality Education in Community Schools: A Case Study of Sarlahi District, Nepal - Panta, Chitra Kumar (Chaturbhujeshwar Academic Journal, 2024)
This study examines the quality of education in government schools of Sarlahi District, Nepal, focusing on factors such as school infrastructure, teaching methodologies, parental involvement and inclusivity. The study adopts a quantitative research approach with a descriptive research design and analyze data collected from students across eight community secondary schools in various municipalities of Sarlahi District. Data were gathered using structured questionnaires to assess perceptions of educational quality, discrimination, gender equality and the availability of learning resources. The findings reveal significant gaps in teaching quality, infrastructure, and inclusivity, with notable inconsistencies in interactive and child-centered teaching methods. Inadequate science and ICT laboratories, coupled with insufficient skilled manpower, undermine the learning environment. The analysis also highlights limited parental involvement in academic support with economic pressures contributing to conflicting responsibilities of student between household chores and education. Overall, the study emphasizes the need to address these challenges by enhancing teacher training, investing in educational infrastructure and bridging the gap between policy and practice to achieve inclusive, quality education in Sarlahi District.